2022
DOI: 10.3390/ijerph19106025
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Meditation with Stabilization Exercise in Marine Region on Pain, Tactile Sense, Muscle Characteristics and Strength, Balance, Quality of Life, and Depression in Female Family Caregivers of People with Severe Physical Disabilities: A Randomized Single-Blinded Controlled Pilot Study

Abstract: Female caregivers of people with disabilities are burdened physically and mentally. To improve these symptoms, an intervention that is easy to apply and has fewer side effects, such as natural healing, has been proposed, but the effect of healing using marine resources is unclear until now. The purpose of this study is to investigate the effect of meditation accompanied with stabilization exercise in the marine region on the improvement of pain, tactile sense, muscle characteristics, muscle strength, balance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
(83 reference statements)
0
2
0
1
Order By: Relevance
“…Voltar a atenção aos cuidadores, entendendo as barreiras físicas, sociais e emocionais envolvidas no ato de cuidar, torna-se imprescindível no âmbito da saúde coletiva, tanto para proporcionar maior qualidade de vida e menor sobrecarga nos cuidadores como para quem é cuidado (SOUZA et al, 2015). Shin et al (2022), sugerem que a meditação e o exercício físico são eficazes para melhorar a saúde física e mental dos cuidadores de pessoas com deficiência, sendo mostrado nos resultados que a dor foi significativamente reduzida juntamente com a melhora da qualidade de vida e da depressão.…”
Section: Resultsunclassified
“…Voltar a atenção aos cuidadores, entendendo as barreiras físicas, sociais e emocionais envolvidas no ato de cuidar, torna-se imprescindível no âmbito da saúde coletiva, tanto para proporcionar maior qualidade de vida e menor sobrecarga nos cuidadores como para quem é cuidado (SOUZA et al, 2015). Shin et al (2022), sugerem que a meditação e o exercício físico são eficazes para melhorar a saúde física e mental dos cuidadores de pessoas com deficiência, sendo mostrado nos resultados que a dor foi significativamente reduzida juntamente com a melhora da qualidade de vida e da depressão.…”
Section: Resultsunclassified
“…This study's results revealed that the hospitalized elderly with normal muscle strength had a higher level of mindfulness than those with abnormal muscle strength (P < 0.05), possibly because the elderly with abnormal muscle strength are more prone to depression [19]. The elderly can easily lead to impaired daily activities and loneliness due to abnormal muscle strength [37].…”
Section: In Uencing Factors Of Mindfulness Level In Elderlymentioning
confidence: 99%
“…Strength training has anti-inflammatory properties [ 31 ], aids in beneficial changes in body composition [ 32 ], and makes weight management easier [ 33 ]. In addition, muscle strength seems to be inversely correlated with depression and cognitive performance in middle-aged and older adults [ 34 , 35 ], emphasising the value of exercise and physical fitness in preventing depression. Grip strength (GS), the force used by the hand and fingers to grasp and hold onto an object, is a numerical assessment of the strength of the muscles used in handgrip activities [ 36 ].…”
Section: Introductionmentioning
confidence: 99%